2017
DOI: 10.1123/ijspp.2016-0436
|View full text |Cite
|
Sign up to set email alerts
|

Validity, Sensitivity, Reproducibility, and Robustness of the PowerTap, Stages, and Garmin Vector Power Meters in Comparison With the SRM Device

Abstract: The PWT, STG, and VCT systems appear to be reproducible, but the validity, sensitivity, and robustness of the STG and VCT systems should be treated with some caution according to the conditions of measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
56
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(70 citation statements)
references
References 30 publications
13
56
1
Order By: Relevance
“…In order to monitor the power output during both HIT sessions, the bike was equipped with a PowerTap SL 2.4 power meter (CycleOps, Madison, USA) mounted on the rear wheel. The PowerTap device is a valid and reliable power meter during both vibration and no‐vibration conditions . In order to give resistance to the back wheel, the bike was connected to a Computrainer LabTM electromagnetically braked ergometer (Race Mate, Seattle, WA, USA), calibrated according to the manufacturer's specifications, which was attached to a vibration plate (Pneu‐Vibe Pro; Pneumex, Inc. Sandpoint, ID, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In order to monitor the power output during both HIT sessions, the bike was equipped with a PowerTap SL 2.4 power meter (CycleOps, Madison, USA) mounted on the rear wheel. The PowerTap device is a valid and reliable power meter during both vibration and no‐vibration conditions . In order to give resistance to the back wheel, the bike was connected to a Computrainer LabTM electromagnetically braked ergometer (Race Mate, Seattle, WA, USA), calibrated according to the manufacturer's specifications, which was attached to a vibration plate (Pneu‐Vibe Pro; Pneumex, Inc. Sandpoint, ID, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Novak and Dascombe [6] studied 21 male cyclists and while there were large variances for 5 second maximal effort sprints, similar to our results no significant differences were found. However, Bouillod et al [7] found significantly lower power output for the VPM in the 53/19 gear ratio. Over a variety of maximal effort sprints between 5 and 600 seconds, Novak and Dascombe [6] found the VPM overestimated power output.…”
Section: Validitymentioning
confidence: 94%
“…This difference may be due to the maximal effort versus constant effort testing protocols. Bouillod et al [7] did not find significant differences during constant power tests, but used a cycling treadmill versus more traditionally accepted cycling trainers and varied wattages by adding weight via water bottles to the cyclist's bicycle.…”
Section: Validitymentioning
confidence: 99%
See 2 more Smart Citations